Influence of humidity on kinetics of xylene adsorption onto ball-type hexanuclear metallophthalocyanine thin film - DUMLUDAĞ, FATİH (ELSEVIER, 2015)
The effects of relative humidity on baseline conductivity, xylene sensitivity and adsorption kinetics of xylene vapor on hexylthiometallophthalocyanines substituted ball-type hexanuclear metallophthalocyanine thin film have been studied. The first results showed that the presence of humidity, acting as interference gas, modifies both the baseline conductivity and sensitivity of the film toward xylene vapor. Three kinetic models, the first-order equation, the Elovich model and the Ritchie's equation were selected to follow the adsorption process. The rate constants, equilibrium capacities and related correlation coefficients for each kinetic model were calculated and discussed. The first-order equation was the best of the various kinetic models studied to describe the adsorption kinetic of xylene on Pc film in humid conditions, as evidenced by the highest correlation coefficients. On the other hand, it was observed that Elovich equation generates a straight line that best fit to the data of adsorption of xylene on Pc film in dry atmosphere. (C) 2015 Published by Elsevier B.V.
Keywords: Xylene sensing; Adsorption kinetics; Sensitivity; Elovich; Ritchie; NITROGEN-DIOXIDE EXPOSURE; SENSING PROPERTIES; ROOM-TEMPERATURE; ELOVICH EQUATION; BENZENE; SENSORS; TOLUENE; SO2; CO